Rancang Bangun Aplikasi Informasi Produk Baja Berbasis Android Dengan Fitur Pencarian Dan Penilaian - Buana, Aldi Wahyu; Sujana, Dadang; Windyasari, Vina Septiana (Universitas Islam Syekh Yusuf Tangerang, 2025)
The advancement of mobile technology has encouraged the use of android applications as a solution for delivering fast and efficient information, including in the steel industry sector such as that experienced by PT xwz, where the Sales division faces obstacles in delivering product information manually which causes delays and inaccuracies in data. Therefore, this study aims to design and build an android-based steel product information application with search and assessment features to make it easier for customers to access complete, accurate, and real-time product data. In designing the system, the prototype method is used to develop this application. The application design is supported by the Unified Modeling Language (UML) to describe the application flow in detail. Application testing is carried out using the black box method to ensure application functionality. In addition, questionnaire testing was also carried out involving 10 respondents consisting of 8 customers and 2 admin staff using the System Usability Scale. The results of the satisfaction score survey were 72%, indicating that this application is included in the good category. Indicating that the application is considered worthy of being used as an information media and supporting the sales process at PT xwz.